Effect of Strategic Management to Enhance Adaptability to Change in Management Consulting Companies - AlNajem, Hosam Salem Ibrahim (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This study addresses how strategic management helps management consulting firms in Saudi Arabia adapt better to changes. It fills an important gap in understanding how strategic approaches boost a company's resilience and ability to learn continuously in fast changing environments. The research focuses on identifying which parts of strategic management like planning, vision, innovation, and resource use most effectively promote adaptability, which we measure through resilience and ongoing learning. What's special about this study is that it centers on Saudi Arabia's consulting scene, a sector that’s developing quickly under Vision 2030. The insights gained here could also be useful for other industries worldwide that face swift changes. For this research, a survey was done with 108 employees from a Saudi consulting firm. The data was analyzed using basic statistics and regression techniques. The findings indicate that managing innovation (β=0.677, p<0.001) and resources (β=0.424, p<0.001) have the biggest positive impact on resilience. Similarly, resource management (β=0.92, p=0.02) and innovation (β=0.42, p=0.04) considerably support continuous learning. Interestingly, having a strong strategic vision showed a noticeable effect on resilience (β=1.23, p=0.02). On the other hand, traditional strategic planning didn’t seem to have a meaningful influence on adaptability (p>0.05). To summarize, the ability to adapt in consulting firms depends more on flexible skills like innovation and agile resource use than on strict planning. The study recommends promoting a culture of innovation, developing flexible resource systems, and continuously encouraging learning. Policymakers can help by offering R&D incentives to support these efforts. Overall, this work provides a framework for companies dealing with uncertainty and aligns with Vision 2030’s goals for economic diversification. Future research should look into sector-specific strategies for adaptability and explore how leadership influences these processes